PERANCANGAN ULANG INSTALASI LISTRIK DI GEDUNG LABORATURIUM TEKNOLOGI HASIL PERKEBUNAN POLITEKNIK NEGERI KETAPANG - Melli, Melli; Normansyah, Normansyah; Jimmi Rizaldi, Muhammad (Electrical Network Systems and Sources, 2024)
This final project is entitled "Redesign of Electrical Installations in the Plantation Technology Laboratory Building of Ketapang State Polytechnic." This study aims to redesign the electrical installations in the laboratory building to make them more efficient and safe. The methodology used includes analysis of existing conditions, calculation of electricity needs, and redesign of electrical installations in accordance with applicable standards. The results of this study are expected to provide optimal solutions in meeting the electricity needs of buildings, improving safety, and energy efficiency. The redesign of the installation must meet existing provisions and meet the things based on: reliability, accessibility, availability, beauty, security, and economy. The problem discussed is the redesign of electricity in the plantation technology laboratory building of Ketapang State Polytechnic including the number of light points and power installations including conductor sockets in the laboratory building. Keywords: Electrical Installation, Redesign, Energy Efficiency, Safety, Laboratory